Níveis de fósforo e inoculação de sementes por Bacillus megaterium (CNPMS B119) e Bacillus subtilis (CNPMS B2084) no crescimento e desenvolvimento de plantas de soja - Giovelli, Jéssica (2022)
Phosphorus (P) is a fundamental element in plant metabolism and a limiting nutrient for agricultural production in tropical soils. Practices aimed at increasing the efficiency of this nutrient are essential. The aim of the study was to evaluate whether seed inoculation with Bacillus megaterium (CNPMS B119) and Bacillus subtilis (CNPMS B2084) affects the growth and development of soybean plants and increases P solubilization in different soils. The experiment was carried out in a greenhouse at the Federal University of Santa Maria, RS. The treatments consisted of a factorial 5 (P levels: 0%, 25%, 50%, 75% and 100% of the recommended dose) x 2 (with and without inoculant) x 2 (Oxisol with silty clay texture and Argisol with loamy texture). A completely randomized design was used with 4 replications, each consisting of 3 pots. The following parameters were evaluated: plant height and physiological attributes at phenological stages V4, R2 and R5; acid phosphatase enzyme activity, chlorophyll a, chlorophyll b, chlorophyll total and carotenoids content, morphological parameters of the root system, root and shoot dry mass, tissue P content and leaf area at stage R2. At the end of the crop cycle (R8 stage) the number and mass of grains produced in each plant, weight of a thousand grains, and seed vigor were evaluated. The residual P content in the soil was also analyzed. The data obtained were submitted to analysis of variance (ANOVA) and subsequently to Tukey's test (p≤0.05) to compare the means of qualitative treatments and regression analysis for quantitative treatments. The results obtained indicated that: seed inoculation with B. megaterium and B. subtilis did not interfere the growth and development of soybean plants, regardless of the type of soil used; seed inoculation with B. megaterium and B. subtilis did not influence the solubilization of fixed phosphorus in the soil and its utilization efficiency; the physiological, morphological and productivity parameters of soybean plants were positively influenced by the increase in P levels, and this response was influenced by the type of soil. Therefore, under the conditions of this work, seed inoculation with B. megaterium (CNPMS B119) and B. subtilis (CNPMS B2084) did not positively affect the growth and development of soybean plants and did not increase P solubilization in different soils.